Evolution of PV systems in Greece and review of applicable solutions for higher penetration levels. (August 2017) - Kyritsis, A.; Voglitsis, D.; Papanikolaou, N.; Tselepis, S.; Christodoulou, C.; Gonos, I.; Kalogirou, S.A.
Abstract: The European Directive regarding the promotion of energy from renewable sources (Directive 2009/28 EC) specifies separate national targets for each member state of the EU community, in order at least 20% of EU total energy demands to be met by renewable energy sources by 2020. The analysis performed in this work highlights that grid connected photovoltaic (PV) systems bring remarkable energy benefits to the electricity supply of Greece, meeting in parallel its national targets. This is validated with data reported from the operator of Hellenic Electricity Market (LAGIE). On the other hand a mass energy production coming from PV systems without energy storage units and sufficient electricity network architectures is liable to cause severe disturbances to the Greek electricity network. This issue is acknowledged by representative data from the Hellenic Electricity Power Transmission and Distribution Network Operators (ADMIE and HEDNO). Furthermore, sustainable and innovative electricity network architectures (such as micro-grids, smart-grids and web of cells), as well as innovative intermittent Renewable Energy Sources (RES) stabilization techniques are discussed, in order to facilitate high PVs integration level. Highlights: Grid connected PVs provide more than 7% of the Greek annual electricity demand. PVs generate at least 38% of RES total electricity production for 6 months every year. The intermittent nature of PVs causes severe disturbances to the Greek electric system. Sustainable electricity network architectures are reviewed for higher PVs integration. Innovative intermittent RES stabilization techniques are highlighted.